Feasibility and safety of a novel plastic stent designed specifically for endoscopic ultrasound-guided pancreatic duct drainage - Fukuda, Soma; Hijioka, Susumu; Nagashio, Yoshikuni; Maruki, Yuta; Ohba, Akihiro; Agarie, Daiki; Hagiwara, Yuya; Hara, Hidenobu; Okamoto, Kohei; Yamashige, Daiki; Yagi, Shin; Kuwada, Masaru; Chatto, Mark; Kondo, Shunsuke; Morizane, Chigusa; Ueno, Hideki; Saito, Yutaka; Okusaka, Takuji (Endoscopy International Open, 2024)
Background and study aims Endoscopic ultrasound-guided pancreatic duct drainage (EUS-PD) is emerging as an effective alternative treatment for obstructive pancreatitis after unsuccessful endoscopic retrograde pancreatography (ERP). However, the high incidence of adverse events associated with EUS-PD (approximately 20%) remains an issue. Recently, we developed a novel plastic stent for EUS-PD, with a radiopaque marker positioned at approximately one-third of the length from the distal end of the stent and side holes positioned exclusively distal to the marker. This study aimed to evaluate the feasibility and safety of using this stent in EUS-PD.Patients and methods We retrospectively reviewed data from 10 patients who underwent EUS-PD with the novel plastic stent at the National Cancer Center Hospital between March 2021 and October 2023. Technical and clinical success, procedure times, adverse events (AEs), recurrent pancreatic duct obstruction (RPO), and time to RPO were assessed.Results Of the 10 patients, five had postoperative benign pancreaticojejunal anastomotic strictures and five had malignant pancreatic duct obstruction. The technical and clinical success rates were both 100% (10/10). An AE (self-limited abdominal pain) occurred in one patient (10.0%). Two patients (20.0%) died of their primary disease during the follow-up period (median, 44 days; range, 25–272 days). The incidence of RPO was 10.0% (1/10), and the 3-month non-RPO rate was 83.3%.Conclusions The novel plastic stent shows potential as a useful and safe tool in EUS-PD.
Keywords: Pancreatobiliary (ERCP/PTCD); Strictures; Endoscopic ultrasonography; Pancreas; Intervention EUS